Portulaca oleracea L. organic acid extract inhibits persistent methicillin-resistant Staphylococcus aureus in vitro and in vivo - Liu, Gengsong; Liu, Aijing; Yang, Cheng; Zhou, Congcong; Zhou, Qiaoyan; Li, Haizhu; Yang, Hongchun; Mo, Jiahao; Zhang, Zhidan; Li, Gonghe; Si, Hongbin; Ou, Changbo (Frontiers in Microbiology, 2023)
Staphylococcus aureus continues to be one of the most important pathogens capable of causing a wide range of infections in different sites of the body in humans and livestock. With the emergence of methicillin-resistant strains and the introduction of strict laws on antibiotic usage in animals, antibiotic replacement therapy has become increasingly popular. Previous studies have shown that Portulaca oleracea L. extract exerts a certain degree of bacteriostatic effect, although the active ingredients are unknown. In the present study, the antibacterial activity of the organic acid of P. oleracea (OAPO) against S. aureus was examined using a series of experiments, including the minimum inhibitory concentration, growth curve, and bacteriostasis curve. In vitro antibacterial mechanisms were evaluated based on the integrity and permeability of the cell wall and membrane, scanning electron microscopy, and soluble protein content. A mouse skin wound recovery model was used to verify the antibacterial effects of OAPO on S. aureus in vivo. The results showed that OAPO not only improved skin wound recovery but also decreased the bacterial load in skin wounds. Moreover, the number of inflammatory cells and cytokines decreased in the OAPO-treated groups. In summary, this study reports a botanical extract that can inhibit S. aureus in vitro and in vivo, indicating the potential use of OAPO to prevent and control S. aureus infection in the near future.